Power Structures and Religious Legitimacy: The Influence of Dayah Ulama in the Politics of Aceh Analyzed using Powercube Theory - Muntasir, Muntasir; Zulkarnaen, Iskandar; Aminullah, Muhammad; Hamdani, Muslem; Hidayat, Bimby (SCAD Independent, 2025)
The existence and traces of involvement of dayah ulama in the power dimension have placed them as religious leaders and political actors. Resulting in vertical mobility in policy making. The research subjects were dayah ulama and religious leaders in Aceh. This study aimed to understand the dimensions of the political power of Acehnese ulama working at the level, space, and form. This research used qualitative methods based on interview data, questionnaires, and literature studies. The results showed that the ulama dayah had a lot of capital and power to build power. These dimensions could be classified as follows: 1) the level dimension in the power structure of ulama was very central and able to influence local and even national political constellations; 2) with personal qualities and public belief in the Keuramat (sacred) and temeureuka (damned) owned by the ulama, indicating the legitimacy of power in the form of “visible and invisible power” in the Aceh ulama; 3) through dayah institutions, networks of religious organizations and the Ulema Consultative Assembly had provided ample space for Aceh ulama to build their identity and power as holders of religious and social authority in the public sphere.